Desenvolvimento territorial rural: análise comparada entre os territórios constituídos autonomamente e os induzidos pelas políticas públicas no Brasil e na Espanha - Jesus, Clesio Marcelino de (2013)
In the last two decades territorial approach has been used as an instrument from public policies to improve development, especially, rural development in all Latin America and particularly in Brazil. This thesis aims to identify and demonstrate in which conditions territorial development is possible. For that, it was done a revision on the change of perspective from the growth to economic development highlighting the changing emphasis of the role of the state in the conduct of public policies. Afterwards, as unfolding of the crisis of the 1970s and 1980s and the process of democratization in the country we observe the incorporation of decentralizing proposals of public management. The policies whose theoretical and ideological reference is the neoliberalism earn emphasis, which led to use the local or territorial approach in conducting development policies in the country in order to encourage endogenous development. From these conditions, we carried out a comparative study on distinct territorial experiences in Brazil and in Spain, divided in two groups. In the first one, formed by the autonomously-conducted territories, in Brazil, we analyzed the experience of Cerrado Mineiro Coffee Territory and, in Spain, the Los Pedroches territory. In the second group, formed by the public policies induced territories, in Brazil, we analyzed the Noroeste de Minas territory, induced by the Secretary of Territorial Development of Agrarian Development Ministry, further modified to Citizen Territory. In Spain, the Medio Guadalquivir e Guadajoz y Campiña Este de Córdoba territories, induced by European Union Programs LEADER and PRODER. Therefore, the search methodology used as proceedings: theoretical and historical revision, case study with compared analysis, survey of primary and secondary information using qualitative and quantitative data as well processing and analysis of the results. Our study allowed us to conclude that a policy of rural territorial development induction is an important instrument to promote communities of depressed economies (disadvantaged in European terminology). However, it is insufficient the mere induction to constitute social and productive arrangements with the responsibility to carry out a diagnosis of territorial reality and to elaborate a project in order to favor a territorial pact creation and management. Besides the social and political conditions, not always found in Brazil induced by taking European territories, induced and autonomous, we verified the need of various infrastructural conditions (physic and human) for this national experience succeeds. Although we recognize the orientation change of the State role in this process, with the Citizen Territories, we conclude that it is necessary a reformulation in the rural territorial development policy in Brazil, form an adequate induced territory design till a better articulation of the different public organs in territorial actions.